Ocular Motor and Sensory Function in Parkinson's Disease - Almer, Zina; Klein, Kathyrn S.; Marsh, Laura; Gerstenhaber, Melissa; Repka, Michael X. (Ophthalmology (Rochester, Minn.), 2012)
To evaluate the effect of dopaminergic medication and deep brain stimulation on ocular function in Parkinson's disease (PD) and to measure vision-related quality of life in subjects with PD. Prospective, comparative case series. Twenty-seven PD and 16 control subjects were recruited. Visual acuity, ocular motor function, convergence, and vision-related quality of life using the 25-item National Eye Institute Visual Function Questionnaire (VFQ-25) were measured. Visual sensory and motor measurements were obtained during the on and off states of PD dopaminergic treatment. Convergence ability and vision-related quality of life. The PD subjects had a mean age of 58.8 years; 30% were female. Their mean duration of PD was 10.9±6.8 years. The control subjects had a mean age of 61.6 years; 56% were female. There was no difference in visual acuity, contrast sensitivity, or color vision of the PD subjects in their on state compared with controls. Convergence amplitudes measured with base-out prism were significantly poorer in PD subjects in their on state compared with controls (24.1±8 Δ vs. 14.8 ±10.3 Δ; P = 0.003). The mean composite VFQ-25 score was significantly worse in the PD subjects compared with the controls (87.1±8.69 vs. 96.6±3.05; P = 0.0001). Comparing the PD subjects in their on with their off states, there was no difference in distance exodeviation, near exodeviation, or ocular ductions. Mean convergence amplitudes and near point of convergence were better in the on state compared with the off state: 14.8±10.3 Δ versus 10.7±9.0 Δ (P = 0.0006) and 13.1±9.1 cm versus 18.1±12.2 cm (P = 0.002), respectively. Convergence ability is significantly poorer in PD subjects in both the on and off states compared with controls, but improves significantly with systemic dopaminergic treatment. Ocular motor function in PD subjects fluctuates in response to treatment, which complicates ophthalmic management. Parkinson's disease subjects have a significant reduction in vision-related quality of life, especially with near activities, that is not associated with visual acuity. The author(s) have no proprietary or commercial interest in any materials discussed in this article.